2021
DOI: 10.3390/healthcare10010057
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Requirements and Unmet Needs of Informal Caregivers of Patients with End-Stage Kidney Disease (ESKD) Receiving Haemodialysis: A Narrative Review

Abstract: Background: Patients with end-stage kidney disease receiving haemodialysis rely heavily on informal caregivers to support them living at home. Informal caregiving may exact a toll on caregivers’ physical, emotional, and social well-being, impacting negatively on their overall quality of life. The aim of this narrative review is to report knowledge requirements and needs of informal caregivers of patients with end stage kidney disease (ESKD) receiving haemodialysis. Methods: The review followed the Preferred Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
3
7
1
Order By: Relevance
“…In accordance with the findings of a study, Rwandan family caregivers expressed personal satisfaction and a sense of responsibility as their motives in care provision 6. In previous studies, religion and spirituality as a coping strategy mainly emanated in the Islamic context 30. In contrast, the present study provides a new ground for coping through religion such as Buddhism.…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with the findings of a study, Rwandan family caregivers expressed personal satisfaction and a sense of responsibility as their motives in care provision 6. In previous studies, religion and spirituality as a coping strategy mainly emanated in the Islamic context 30. In contrast, the present study provides a new ground for coping through religion such as Buddhism.…”
Section: Discussionsupporting
confidence: 89%
“…They found that caregivers who reported social isolation, chronic health problems, and little time for self-care had more severe levels of burden than those who did not have chronic health problems. Additionally, this result was consistent with Matthews et al, (2021). They studied "Knowledge Requirements and Unmet Needs of Informal Caregivers of Patients with End-Stage Kidney Disease (ESKD) Receiving Hemodialysis: A Narrative Review."…”
Section: Effect Of Family Centered Empowerment Intervention On Burden...supporting
confidence: 80%
“…Caregivers indicated interest in most suggested intervention topics, including living with CKD, support services for caregivers, physical health, and diet. A review of information needs among caregivers of people with end-stage kidney disease [ 66 ] found that caregivers had a number of unmet information needs and generally did not receive enough information about practical aspects of caring for someone with CKD or understanding the condition. Available information was considered generic and not tailored to the needs of caregivers of people with CKD [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of information needs among caregivers of people with end-stage kidney disease [66] found that caregivers had a number of unmet information needs and generally did not receive enough information about practical aspects of caring for someone with CKD or understanding the condition. Available information was considered generic and not tailored to the needs of caregivers of people with CKD [66]. Tailoring interventions, in terms of content and delivery format, could be a way to meet caregiver's varied needs, and appears important to enhance acceptability [67][68][69].…”
Section: Cbt Self-help Intervention Preferencesmentioning
confidence: 99%